Secure Code Generation for Multi-Level Mutual Authentication - Gregor Alexander Aramice; Jaafar Qassim Kadhim (Universitas Ahmad Dahlan, 2018)
Any secured system requires one or more logging policies to make that system safe. Static passwords alone cannot be furthermore enough for securing systems, even with strong passwords illegal intrusions occur or it suffers the risk of forgotten. Authentication using many levels (factors) might complicate the steps when intruders try to reach system resources. Any person to be authorized for logging-in a secured system must provide some predefined data or present some entities that identify his/her authority. Predefined information between the client and the system help to get more secure level of logging-in. In this paper, the user that aims to log-in to a secured system must provide a recognized RFID card with a mobile number, which is available in the secured systems database, then the secured system with a simple algorithm generates a One-Time Password that is sent via GSM Arduino compatible shield to the user announcing him/her as an authorized person.